2019
DOI: 10.1097/md.0000000000017520
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different carbon dioxide (CO2) insufflation for laparoscopic colorectal surgery in elderly patients

Abstract: Background:Evidence suggests that dry CO2 insufflation during laparoscopic colorectal surgery results in greater structural injury to the peritoneum and longer hospital stay than the use of warm, humidified CO2. We aimed to test the hypothesis that warm, humidified CO2 insufflation could reduce postoperative pain and improve recovery in laparoscopic colorectal surgery.Methods:One hundred fifty elderly patients undergoing laparoscopic colorectal surgery under general anesthesia from May 2017 to October 2018 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…In a randomized and controlled trial of 44 women undergoing deep endometriosis surgery, a decreased degree of adherence formation was found by inducing the pneumoperitoneum with a cooled and humidified gas composed of a mixture of 86% CO 2 , 10% N 2 O, and 4% O 2 [78]. ese findings are in accordance with the clinical report of reduced pain complaint, length of stay, and analgesic use in subjects receiving heated humidified CO2 compared to those treated with dry CO2 [79].…”
Section: Adhesion Developmentsupporting
confidence: 75%
“…In a randomized and controlled trial of 44 women undergoing deep endometriosis surgery, a decreased degree of adherence formation was found by inducing the pneumoperitoneum with a cooled and humidified gas composed of a mixture of 86% CO 2 , 10% N 2 O, and 4% O 2 [78]. ese findings are in accordance with the clinical report of reduced pain complaint, length of stay, and analgesic use in subjects receiving heated humidified CO2 compared to those treated with dry CO2 [79].…”
Section: Adhesion Developmentsupporting
confidence: 75%
“…Additionally, warmed and humidified CO 2 insufflation leads to an improved body core temperature (BCT) maintenance, a reduction of the inflammatory and cytokine responses (58,59) and improved quality of postoperative course, compared with standard insufflation (60,61). Also, it can reduce intraoperative hypothermia, coagulation dysfunction, early postoperative cough pain, days to first flatus and solid food intake, and the length of hospital stays (62). In recent years, CO 2 -based technologies have accordingly gained considerable interest in the pharmaceutical industry.…”
Section: Inhaled Carrier Gas Delivery Systemmentioning
confidence: 99%
“…Normally it is used not humidified and at room temperature (20–22 °C). Some groups evaluated the effects of insufflated CO 2 on intraoperative body temperature as well as on postoperative pain and length of hospital stay [ 15 , 21 ]. The two meta-analyses of Dean et al and Balayssac et al were able to show positive effects of warmed, humidified CO 2 compared to controls without warming [ 16 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two meta-analyses of Dean et al and Balayssac et al were able to show positive effects of warmed, humidified CO 2 compared to controls without warming [ 16 , 21 ]. Jiang et al, however, demonstrated that warmed, humidified CO 2 or combined forced air warming with CO 2 at room temperature are equivalent [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation